Carnations : poems - Carelli, Anthony, 1979- (Princeton series of contemporary poets., 2011)
In Anthony Carelli's remarkable debut, Carnations, the poems attempt to reanimate dead metaphors as blossoms: wild and lovely but also fleeting, mortal, and averse to the touch. Here, the poems are carnations, not only flowers, but also body-making words. Nodding to influences as varied as George Herbert, Francis Ponge, Fernando Pessoa, and D.H. Lawrence, Carelli asserts that the poet's materials--words, objects, phenomena--are sacred, wilting in the moment, yet perennially renewed. Often taking titles from a biblical vocabulary, Carnations reminds us that unremarkable places and events--a ga.